MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) AS A GROWTH ENGINE - VIJ, ANJALI (IJRDO - Journal of Business Management, 2017)
Many of us still think that it is large companies that still dominate. However it is actually those  Small units which are the backbone of the National Economic Structure. MSME contribute around 6.11% of the manufacturing GDP and 24.63% of the GDP from Service activities as well  as 33.4% of India’s manufacturing output. (www.cii.in) SME has several advantages like it provides employment, it helps in making growth Inclusive, contributes to Balance Regional Development etc. However there is a major obstacle to the growth Of SMEs is its Lack of  adequate Finance. This paper examines various other issues like poor infrastructure; Low Productivity etc and various initiatives taken up by Government of India. This paper also elaborates importance of SMEs for the growth and development of economy